KONSEP ADAB DALAM MENUNTUT ILMU PADA SURAH AL-MUJADALAH AYAT 11(STUDI KOMPARATIF TAFSIR ULAMA NUSANTARA) - Ihsandi, Diva Alif; Hermanto , Edi (Anfa Mediatama, 2024)
Thisi studyi discussesi thei concepti ofi adabi ini studyingi basedi oni Surahi Al-Mujadalahi versei 11i accordingi toi thei interpretationsi ofi Nusantarai scholars.i Iti aimsi toi analyzei theiri interpretations,i identifyi differencesi andi similarities,i andi providei recommendationsi fori strengtheningi thei valuei ofi adabi ini education.i Thisi studyi exploresi thei contributioni ofi locali scholarsi toi Islamici educationi thati isi contextuali andi relevanti toi Indonesia.i Thisi researchi usesi ai descriptive-analyticali qualitativei methodi toi examinei thei concepti ofi adabi ini studyingi ini Surahi Al-Mujadalahi versei 11i basedi oni thei interpretationi ofi Nusantarai scholars.i Comparativei researchi comparesi thei interpretationsi ofi Buyai Hamka,i Sheikhi Nawawii al-Bantani,i andi KH.i Hasyimi Asy'ari.i Primaryi datai sourcesi comei fromi thei interpretationsi ofi scholars,i whilei secondaryi fromi books,i journals,i andi articles.Thei concepti ofi adabi demandingi knowledgei formsi individuali character,i includingi respecti fori teachersi andi ethicsi betweeni students.i Surahi Al-Mujadalahi versei 11i emphasizesi thei importancei ofi knowledgei withi adab.i Thisi researchi comparesi thei interpretationsi ofi Nusantarai scholarsi toi understandi locali interpretations.i Adabi ini educationi includesi respect,i humility,i andi mutuali appreciation,i contributingi toi sociali progressi andi thei formationi ofi ai knowledgeablei society.Adabi ini demandingi knowledgei isi ani importanti elementi ini Islam,i includingi respect,i diligence,i andi sincerei intentionsi toi geti closeri toi Allah.i Surahi Al-Mujadalahi versei 11i emphasizesi respecti ini thei assemblyi ofi knowledge.i Nusantarai scholarsi suchi asi Hamkai andi Quraishi Shihabi interpreti adabi withi locali culture,i connectingi knowledgei andi moralsi fori individuali andi sociali progress,i especiallyi ini pesantren.